Star Wars. Moving target : a Princess Leia adventure - Castellucci, Cecil, 1969-; Fry, Jason, 1969- (Disney/Lucasfilm Press, 2015)
"In this story, set between Star Wars: The empire Strikes Back and Star Wars: Return of the Jedi, Princess Leia must lead a ragtag group of rebels on a treacherous decoy mission against the evil Galactic Empire."--page 4 of cover.